The Prince of Wales Island Road System: From Logging Roads to State Scenic Byway - Reilly, Marili Green; United States. Department of Transportation. Federal Highway Administration. Office of Federal Lands Highway
When Federal Highway Administration became involved in road building on Prince of Wales Island, it was to create a “backbone” of roads to tie together the existing routes. Thirty years later, there are just over 300 miles of formally designated forest highways on the island, and 260 miles of the road system on the island is designated an Alaska Scenic Byway.